Analisis Determinasi Opini Audit Going Concern - Alfan Harun; Wisnu Julianto; Retna Sari (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
This study is quantitative research to determine the influence of financial distress, debt default, audit tenure against going concern audit opinion. The data collected was secondary data by documentation and literature study. The population of this study is manufactur companies listed in Indonesia Stock Exchange during 2015 – 2018. The sample of this study is 272 chosen by simple random sampling method. The research used logistic regression analysis method. The results of this study showed that financial distress, debt default and audit tenure has no influence against going concern audit opinion. Keywords : Going Concern Audit Opinion, Financial Distress, Debt Default, Audit Tenure